Innovation clusters effects on adoption of a general purpose technology under uncertainty - B. G. Jean Jacques Iritié (National Polytechnic Institute Félix Houphouet Boigny, 2017)
This paper analyzes the effect of innovation clusters on the adoption of a gen- eral purpose technology (GPT) and on firms R&D investment levels in im- perfect information situation. To do this, we developed a theoretical model of vertical relation, described as a four-step game between an upstream firm providing innovative GPT and an innovative downstream associated sector, integrator of this technology. The downstream sector ignores the quality of the GPT and we model the innovation cluster as a coordination mode of firms, improving the probability of the downstream firm to receive information about the quality of the GPT technology. Then, we determine firms equilibria (prices and technological qualities) and we showed that the effect of innovation clus- ters on the choice of qualities, the adoption behavior, levels of investment in R&D as well as that social welfare depends on the quality of R&D activities carried out before the establishment of the cluster and a threshold effect or cluster critical mass; if the critical mass in terms of information sharing and interaction is not reached, the cluster may have negative effects. In other words, the consensual idea of expected positive effects of innovation clusters must be put into perspective.
Keywords: C02; D82; D83; L15; O3; 330; innovation clusters; general purpose technology; technology adoption; technology complementarity; uncertainty; critical mass